Development of quality indicators for the management of Staphylococcus aureus bacteraemia. (8th August 2019) - ten Oever, Jaap; Jansen, Joëll L; van der Vaart, Thomas W; Schouten, Jeroen A; Hulscher, Marlies E J L; Verbon, Annelies
Abstract: Background: Staphylococcus aureus bacteraemia (SAB) is a serious and often fatal infectious disease. The quality of management of SAB is modifiable and can thus affect the outcome. Quality indicators (QIs) can be used to measure the quality of care of the various aspects of SAB management in hospitals, enabling professionals to identify targets for improvement and stimulating them to take action. Objectives: To develop QIs for the management of hospitalized patients with SAB. Methods: A RAND-modified Delphi procedure was used to develop a set of QIs for the management of SAB in hospitalized patients. First, available QIs for the management of SAB were extracted from the literature published since 1 January 2000 (MEDLINE and Embase databases). Thereafter, an international multidisciplinary expert panel appraised these QIs during two questionnaire rounds with an intervening face-to-face meeting. Results: The literature search resulted in a list of 39 potential QIs. After appraisal by 30 medical specialists, 25 QIs describing recommended care at patient level were selected. These QIs defined appropriate follow-up blood cultures ( n =2), echocardiography ( n =6), source control ( n =4), antibiotic therapy ( n =7), antibiotic dose adjustment ( n =2), intravenous-to-oral switch ( n =2), infectious disease consultation ( n =1) and medical discharge report ( n =1). Conclusions: A set of 25 QIs for the management of SAB for hospitalized patients was developed by using a RAND-modified Delphi procedure among international experts. These QIs can measure the quality of various aspects of SAB management. This information can be fed back to the relevant stakeholders in order to identify improvement targets and optimize care.